Exploring the interpersonal dimension of teaching in an Irish post-primary context. Issue 3 (2nd July 2020) - Scully, Darina; Pitsia, Vasiliki; Karakolidis, Anastasios
Abstract : Effective teaching encompasses both a pedagogical and an interpersonal dimension. Despite this, the latter typically receives little attention in initial teacher education and professional development programmes because of its tacit, non-conscious, and context-specific nature. In this study, the interpersonal dimension of teaching was conceptualized in terms of an explicit set of problem-solving strategies. Using the Tacit Knowledge Inventory for High School Teachers (TKI-HS), the perceived effectiveness of these strategies amongst a sample of Irish post-primary teachers ( n = 69) was explored, and the extent to which this varied across certain individual and contextual factors was also investigated. The findings suggest that, when faced with challenging social situations in the course of their professions, Irish post-primary teachers demonstrate preferences for strategies involving either rational discussions with the source of the problem, or appealing to a colleague for advice. These preferences were independent of the teachers' gender, education level, degree of job satisfaction, and the climate of the school in which they worked. Some implications for teacher education programmes are outlined. Potential future directions, including links to broader issues concerning the assessment of non-cognitive skills and competencies more generally, are also discussed.